Synoptic conditions governing upwelling along the Polish Baltic coast - Bartosz Czernecki; Ewa Bednorz; Marek Półrolniczak (Oceanologia)
The study analyses atmospheric feedback to the occurrence of upwelling along the Polish Baltic coast. Upwelling events were identified on the basis of daily mean sea surface temperature (SST) maps from the period 1982-2010 derived from the NOAA OI SST V2 High Resolution Dataset. Synoptic conditions favourable to the occurrence of upwelling were determined on the basis of the NCEP/NCAR reanalysis data. On average, there are approximately 23 days with upwelling each year along the Polish Baltic coast, which account for approximately 13% of the warm period (April-September). The pressure pattern with an anticyclone centred over Scandinavia and extending over northern Europe induces a north-easterly flow of air along the Polish Baltic coast, which causes upwelling. Such a circulation pattern is accompanied by positive air temperature anomalies. The opposite pressure conditions, during which a trough of low pressure encompasses Scandinavia, cause a westerly flow over the southern part of the Baltic basin, which effectively inhibits upwelling along the Polish Baltic coast.